The Influence of Principal Leadership, Work Motivation and Organizational Culture on Teacher Performance in Junior High Schools in Pundong District, Bantul - Titik Kartika Wulan; Khotim Hanifudin Najib (Kuras Institute, 2025)
This study aims to find out and analyze the influence of principals' leadership, work motivation and organizational culture together on teacher performance at the Pundong Bantul Sub-District Middle School. This study began with data collection using questionnaires carried out. The population of this study was all junior high school / MTs teachers amounting to 150 people with sampling using Slovin method taken as many as 110 respondents. Analysis of the data used is the validity and reliability test then testing the assumption test with normality test, heteroscedasticity test and multicollinearity test. Only after that is done a multiple linear regression test. The results of the study, from the regression analysis showed that the three independent variables, namely the principal's leadership, work motivation and organizational culture together had a significant effect on teacher performance in the Pundong Bantul Sub-District Middle School. From partial correlation analysis Most teachers perceive the Principal Leadership in Junior High Schools in Pundong Bantul Subdistrict is still normal, most teachers perceive Organizational Culture in Junior Secondary Schools in Pundong Bantul Subdistrict as usual, most teachers perceive teacher work motivation in Secondary Schools First, the Pundong Bantul Subdistrict is at an ordinary level, most teachers are perceived to have high levels of performance and together leadership, organizational culture and work motivation have a significant influence on teacher job satisfaction in the Pundong Bantul Sub-District Middle School. This is proven from the ANOVA test in the first regression obtained by the F value of 72.552 with a significant level of 0.000